2020
DOI: 10.1002/jsfa.10902
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo digestion comparison of bee pollen with or without wall‐disruption

Abstract: BACKGROUND Bee pollen is considered as a treasure trove of human and animal nutrients as a result of its extensive nutritional and therapeutic properties. However, the sophisticated pollen wall can largely limit the digestibility and bioavailability of these nutrients. RESULTS An ultrasonication and high shear technique was used to break the walls of five species of bee pollen, including rape bee pollen, lotus bee pollen, camellia bee pollen, wuweizi bee pollen and apricot bee pollen. We compared the digestibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The results of in vitro dynamic digestion also showed that the release rates of amino acids, reducing sugars, proteins and fats in bee pollen with smaller particles after wall disruption were higher than those in untreated samples and the digestibility was also improved. 36 Li et al found that the particle size of wheat bran was also negatively correlated with the bioavailability of ferulic acid and sinapic acid. 24 The smaller the particle size of wheat bran, the better the release of ferulic acid and sinapic acid after digestion.…”
Section: Food and Function Papermentioning
confidence: 99%
“…The results of in vitro dynamic digestion also showed that the release rates of amino acids, reducing sugars, proteins and fats in bee pollen with smaller particles after wall disruption were higher than those in untreated samples and the digestibility was also improved. 36 Li et al found that the particle size of wheat bran was also negatively correlated with the bioavailability of ferulic acid and sinapic acid. 24 The smaller the particle size of wheat bran, the better the release of ferulic acid and sinapic acid after digestion.…”
Section: Food and Function Papermentioning
confidence: 99%
“…On the other hand, it caused nutritional loss. Physical treatment with ultrasound and supercritical fluids was successful, but these methods are highly challenging in terms of time, cost, and effort [15]. The supercritical carbon dioxide (CO 2 ) technique was used to extract essential oil from bee pollen using a supercritical CO 2 system at pressures of 13.2-46.8 MPa, temperatures of 33.2-66.8 • C, and CO 2 flow rates of 6.6-23.4 L/h.…”
Section: Consumption Of Bee Pollenmentioning
confidence: 99%
“…Because of their resistant shells, pollen grains have a high tolerance to mechanical force, high temperatures and extreme chemical conditions such as acids, alkalis, enzymes and organic solvents 52 . These features help them withstand the harsh gastric environment and to serve as oral delivery devices [52][53][54][55] . In addition, pollen grains have irregular surface morphologies and show strong mucosal adhesion, leading to longer GI retention time and higher drug bioavailability in comparison to similarly sized synthetic delivery vehicles with a smooth surface 53 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pollen grains have irregular surface morphologies and show strong mucosal adhesion, leading to longer GI retention time and higher drug bioavailability in comparison to similarly sized synthetic delivery vehicles with a smooth surface 53 . Pollens are either totally or partly digested in the GI tract and excreted, depending on their chemical nature and the integrity of the pollen wall 54,55 . To remove the inherent allergic substances in the cavity of pollen grains and to load drugs, a sequence of chemical treatments is applied, including strong acids, strong bases and organic solvents 30 (Fig.…”
Section: Introductionmentioning
confidence: 99%